PEREMPUAN DALAM PANDANGAN ISLAM: ANTARA IDEALITA DAN REALITA - Nashriyah Nashriyah (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2018)
This article is aimed at discussing about the status of women in Islam and investigating whether or not Islam has contributed to the oppression of women all this time. It is uncovered in this article that Islam has never taught people to treat men and women discriminately. Instead, Islam puts women in a very glorious position. There are a lot of verses and hadits showing the notion. The prevailing distortion of many verses and hadits leading to discrimination against women is largely due to literal comprehension and disregarding the historical background or the context of the sacred texts revelation. Therefore, it is necessary that efforts be made to correct the wrong interpretation of Islamic teachings.